'Penetrating' Foreign Lands: Contestations Over African Landscapes. A Case Study from Eastern Zimbabwe. (1st October 1995) - Schmidt, Heike
Abstract : While it was happening, European expansion was often legitimised by evoking frontier images: pioneers setting off from the metropolis, penetrating wilderness in order to open access to resources, like minerals, living-space, and fertile lands. Central to the ideology of the frontier is the notion of 'no-man's land'. These 'pioneers', however, often had to face local inhabitants and their interpretations and uses of this land. Thus it will be argued that contestations over landscape were at the same time battles over the legitimation of European expansion, as well as over local perceptions of this process. Ideologically, contestations by Europeans and Africans become apparent in the sexualisation of landscape. This paper is based on the case study of a Valley in eastern Zimbabwe on the border with Mozambique, and more specifically of two tea estates which were established in the rainforest. Unusually late for the region, European influence in this remote area only began to become significant in the 1950s which were an important turning point regarding land and landscape in the area. These years of great change will be analysed in order to map out different strands of interest by the main parties involved. It will be demonstrated that their readings of landscape translated into contestations over land. A recent example of such a conflict will be given.